2005
DOI: 10.1111/j.1398-9995.2005.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of stem cell factor expression in nasal polyp epithelial cells with aspirin sensitivity and asthma

Abstract: Mast cells constitute a significant proportion of cells infiltrating nasal polyp tissue, and epithelial cells may release stem cell factor (SCF), a cytokine with chemotactic and survival activity for mast cells. We aimed to assess the expression of SCF in human nasal polyp epithelial cells (NPECs) as related to patients' clinical phenotypes. Nasal polyp tissues were obtained from 29 patients [including nine with aspirin (ASA)-hypersensitivity and 12 with bronchial asthma] undergoing polypectomy for nasal obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
2
32
0
2
Order By: Relevance
“…Taken together, these studies demonstrate an important mechanistic role for SCF that correlates to observations in human asthma where an increased expression of SCF in the lung and in serum after allergen challenges was observed and correlated to the severity of disease (11)(12)(13)(14). Thus, a complex network of activation may be emerging with SCF as an important initiating cytokine locally in the lung with its ability to activate IL-25 production during allergic responses as well as contribute to the maturation of the IL-17RB ϩ cells in the lung and/or bone in a Th2 immune environment.…”
Section: Gr1mentioning
confidence: 63%
See 1 more Smart Citation
“…Taken together, these studies demonstrate an important mechanistic role for SCF that correlates to observations in human asthma where an increased expression of SCF in the lung and in serum after allergen challenges was observed and correlated to the severity of disease (11)(12)(13)(14). Thus, a complex network of activation may be emerging with SCF as an important initiating cytokine locally in the lung with its ability to activate IL-25 production during allergic responses as well as contribute to the maturation of the IL-17RB ϩ cells in the lung and/or bone in a Th2 immune environment.…”
Section: Gr1mentioning
confidence: 63%
“…Importantly, SCF and c-kit have been shown to be highly up-regulated in airways of asthmatics (12) as well as in nasal polyps in aspirin-sensitive asthmatics (13), and circulating levels of SCF have been correlated to the severity of asthmatic disease (14). Investigators have also begun examining the role of SCF on eosinophil accumulation and activation.…”
Section: S Tem Cell Factor (Scf)mentioning
confidence: 99%
“…32 Evidence for a role of SCF in human airway disease was supported by studies demonstrating increased SCF expression in nasal polyps of asthmatics and allergic rhinitis patients. 33,34 Additionally, SCF has been implicated as a potential mediator in fibrotic diseases in the kidney and intestine. 34 -37 Recently, the role of SCF has been verified using a chronic Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…20 These original studies were extended by demonstrating that SCF more broadly activates eosinophils for degranulation, mediator release, as well as cytokine and growth factor production, including TGF-b and b-FGF. 21 This general activation pattern indicates the potential role SCF may play in the activation of local fibroblast and structural cell populations for the remodeling of the airway. In addition, the decrease in key inflammatory mediators such as CCL17 when SCF is blocked might reduce the recruitment and activation of Th2 type lymphocytes via CCR4.…”
Section: Anti-scf Attenuates Chronic Allergen Responsesmentioning
confidence: 99%
“…This is supported by data that demonstrated that SCF-stimulated eosinophils had enhanced binding capacity to VCAM-1 and fibronectin, 20 but also appears to initiate a degranulation response and induces pro-fibrotic mediators, leukotrienes and chemokines. 21 Recent data has established increased SCF and c-kit in asthmatic airways 22 and in nasal polyps, 23,24 further supporting a role for SCF/c-kit activation pathways in allergic disease. However, to date no assessment of the role of SCF on chronic allergic disease characterized by severe AHR and peribronchial fibrosis has been performed.…”
mentioning
confidence: 99%